(untitled) (Research, Society and Development, 2025)
This study aimed to experimentally investigate how additional filtration affects image quality (IQ) and the reduction of medical exposure in abdominal radiography. We used aluminum and copper filters of varying thicknesses, configured by filtration indices (FI), inserted into the collimation of a radiographic system. Images were acquired using a semi-anatomical phantom. We measured Kerma in air (Kar) and calculated incident Kerma in air (Ka,i) and entrance Kerma in air (Ka,e). Mean absorbed doses in organs (DT) and effective dose (ED) were simulated using PCXMC 2.0 software. To evaluate IQ, we quantified signal and noise in six regions of interest (ROI) using ImageJ, obtaining signal-to-noise ratios (SNR), contrast-to-noise ratios (CNR), and radiographic contrast (RC). Results showed that adding 3.0 mmAl of filtration (FI7) significantly reduced medical exposures by 54.32%, Ka,e by 42.23%, and ED, while improving RC by 9.31%. There were also reductions in DT for organs like testes (-47.34%), bladder (-42.50%), and liver (-41.36%). Although there was a slight decrease in SNR (-1.22%) and CNR (-18.18%), additional filtration demonstrated a much greater impact on reducing medical exposures than on IQ degradation.